Bentuk Sikap Sosial Positif Siswa di SDN Mojowarno 1 Kabupaten Jombang - Virna Yualitasya Putri Iriani; Desty Dwi Rochmania (Kampus Akademik Publiser, 2024)
This research is motivated by many students at SDN Mojowarno 1 whose positive social attitudes are reduced, because parents work until late afternoon and students have no one to monitor. The government decided to run a Full Day School system, which is a full-day school, so that students' social attitudes can be monitored by teachers at school and when they come home from school can be directly monitored by parents. This approach used in this research is a qualitative approach, meaning that researchers will look at the phenomena that occur in schools and conduct interviews with several teachers related to students' positive social attitudes. In this study, researchers used a qualitative descriptive form of research. The results of this study indicate that the positive social attitudes of students at SDN Mojowarno 1 Jombang Regency are: students' positive social attitudes are reduced towards friends and teachers and obstacles in positive social attitudes, namely sometimes students do not listen to teacher advice and repeat these negative attitudes, so teachers are required to be more creative in giving advice and consequences to students when they make mistakes.